The DSF family of quorum sensing signals: diversity, biosynthesis, and turnover - Zhou, Lian; Zhang, Lian-Hui; Cámara, Miguel; He, Ya-Wen (Elsevier, 2017)
The diffusible signaling factor (DSF)-based quorum sensing (QS) system has emerged as a widely conserved cell–cell communication mechanism in Gram-negative bacteria. Typically, signals from the DSF family are cis-2-unsaturated fatty acids which regulate diverse biological functions. Recently, substantial progress has been made on the characterization of new members of this family of signals. There have also been new developments in the understanding of the biosynthesis of these molecules where dual enzymatic activities of the DSF synthase and the use of various substrates have been described. The recent discovery of a naturally occurring DSF turnover mechanism and its regulation provides a new dimension in our understanding of how DSF-dependent microorganisms modulate virulence gene expression in response to changes in the surrounding environment.